Reasoned opinion on the modification of the existing maximum residue level (MRL) for acetamiprid in apricots and tree nuts - European Food Safety Authority (EFSA Journal, 2013)
Abstract In accordance with Article 6 of Regulation (EC) No 396/2005, Greece, hereafter referred to as the evaluating Member State (EMS), received an application from Nisso Chemical Europe GmbH to set an import tolerance for the active substance acetamiprid in cherries, cucurbits, peaches/nectarines, apricots, peas without pods, plums and tree nuts from United States of America (USA). The EMS drafted an evaluation report in accordance with Article 8 of Regulation (EC) No 396/2005, which was submitted to the European Commission and forwarded to EFSA. EFSA considered only the Maximum Residue Level (MRL) requests submitted for tree nuts and apricots because for all commodities the existing European Union MRLs are set at the same level or higher than the requested import tolerance. According to EFSA the data are sufficient to derive MRL proposals of 0.7 or 0.8 mg/kg for apricots and 0.06 or 0.07 mg/kg for tree nuts. EFSA considers that adequate analytical enforcement methods are available to control the residues of acetamiprid in the commodities under consideration. Based on the risk assessment results, EFSA concludes that the use of acetamiprid on apricots and tree nuts in USA will not result in a consumer exposure exceeding the toxicological reference values and therefore is unlikely to pose a consumer health risk.